2014
DOI: 10.1093/mnras/stu2430
|View full text |Cite
|
Sign up to set email alerts
|

Luminous blue variables are antisocial: their isolation implies that they are kicked mass gainers in binary evolution

Abstract: Based on their relatively isolated environments, we argue that luminous blue variables (LBVs) must be primarily the product of binary evolution, challenging the traditional single-star view wherein LBVs mark a brief transition between massive O-type stars and Wolf-Rayet (WR) stars. If the latter were true, then LBVs should be concentrated in young massive clusters like early O-type stars. This is decidedly not the case. Examining locations of LBVs in our Galaxy and the Magellanic Clouds reveals that, with only… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
329
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(345 citation statements)
references
References 138 publications
(190 reference statements)
15
329
1
Order By: Relevance
“…Recent work by Smith & Tombleson (2015) on luminous blue variable (LBV) stars provides additional evidence for WC stars being less massive than WN stars.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Smith & Tombleson (2015) on luminous blue variable (LBV) stars provides additional evidence for WC stars being less massive than WN stars.…”
Section: Discussionmentioning
confidence: 99%
“…Smith & Tombleson (2015) found that LBV stars are statistically more isolated than O and WR stars in the Galaxy and in Large Magellanic Cloud clusters, indicating that LBVs cannot in all cases be a phase in the evolution of O and WR stars. They proposed alternative binary scenarios for at least a fraction of the objects.…”
Section: Luminous Blue Variablesmentioning
confidence: 99%
“…This discovery suggests that many massive star phenomena are related to the presence of a binary companion, for example, type Ib and Ic supernovae (Podsiadlowski, Joss, & Hsu, 1992;Smith et al, 2011a) or phenomena such as luminous blue variables (Smith & Tombleson, 2015). Additionally, the recent detection of gravitational waves has confirmed the existence of binary black holes (Abbott et al, 2016d), which are a likely end-product of the most massive binary evolution.…”
Section: Introductionmentioning
confidence: 97%
“…In M33, there are only four confirmed LBVs (Hubble-Sandage variables B, C and 2 and Var 83; Humphreys et al 2014), but we include them as well (the actual number of LBV stars in M33 was estimated to be in the hundreds by Massey et al 2007). As Smith & Tombleson (2015) (Wenger et al 2000), with a search radius of 5 degrees from the centre of the LMC as reported in NED. With such a search we have obtained the coordinates of main-sequence stars between the B2V and O3V spectral types as reported in April 2015.…”
Section: Other Evolved Starsmentioning
confidence: 99%
“…A12 argued that while the diversity within the subtype allows for some progenitors to be LBVs, most IIn progenitors are instead lower-mass stars, such as asymptotic giant branch (AGB) stars exploding as electron-capture SNe. To reconcile this with the identified massive LBV progenitors of type IIn SNe, Smith & Tombleson (2015) examined the LBVs in the Large Magellanic Cloud (LMC) and found them to be relatively isolated from O-type stars, which was argued to at least partially explain the weak correlation with H α emission for the SNe. However, Humphreys et al (2016) pointed out that this LBV sample included both classical and lower-luminosity Original continuum-subtracted H α intensity maps used in this study: the LMC on the left (from the SHASSA survey; Gaustad et al 2001) and M33 on the right (Hoopes & Walterbos 2000), cropped in the case of the LMC but otherwise unaltered.…”
Section: Introductionmentioning
confidence: 99%